Implementasi PTSL Sebagai Upaya Pencegahan Konflik Pertanahan Di Kecamatan Ingin Jaya Kabupaten Aceh Besar - M. Syuib; Sarah Diana Aulia (Law Department, Sharia and Law Faculty., 2021)
In order to guarantee legal certainty for land rights holders, the Government is conducting land registration program throughout Indonesia territory. The program has put an obligation to the land rights holder to register their land. The purpose of land registration is, to provide evidence for the ownership of land. The implementation mechanism of the program in regulated in the Permen ATR/BPN Number 6 of 2018 concerning Complete Systematic Land Registration (PTSL). The presence of the Permen is, in order to prevent land disputes in the community by accelerating land registration. Sub-district of Ingin Jaya, which is located in the Aceh Besar district, is one of the areas where PTSL activities are carried out. Currently, there is a large area of land in the Aceh Besar district has not been certified yet, it may cause legal uncertainty for land owner and such condition can potentially lead to land dispute. One of the indicators to claim this, are by taking land dispute cases as put on trial in the Jantho Court which has reached 32 cases from 2014 until 2019. This study aims to find out how the implementation of PTSL and its barrier in the Sub-District of Ingin Jaya, Aceh Besar. The research method is an empirical juridical research; it works by conducting observations, interviews, and documentation. The result found that the implementation of PTSL in the Sub-District of Ingin Jaya, Aceh Besar, is in accordance with Permen ATR/BPN No. 6 of 2018. However, in the ground, it is found that there are a number of obstacles which affect the successful of the PTSL program both internally and externally. Therefore, synergy and cooperation with all parties are needed so that the PTSL program in the Sub-District of Ingin Jaya can be implemented successfully in order to provide legal certainty for land rights holders, so that the land dispute can be prevented as early as possible.